Ethnic diversity in start-ups and its impact on innovation - Udo Brixy; Stephan Brunow; Anna D'Ambrosio (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
The study analyses the impact of different ethnic compositions of start-ups in Germany on the innovativeness of the new businesses. We are able to distinguish between the ethnicity of the founders and that of the early employees following new results that demonstrate the importance of including all new firms' stakeholders for the firm's success. We make use of a measure introduced by Ruef (2002) and Ruef et al. (2003) which not only takes into account the number of different ethnicities involved, but also includes the unusualness of the ethnic compositions. Our results first reveal that foreigners are an important source of both entrepreneurs and employers. Second, we can show that only really rare combinations, of the founders and employees together, lead to more innovative businesses whereas the more common minorities are even found to have a negative impact on firms' innovativeness. – – Diese Studie untersucht den Einfluss der ethnischen Zusammensetzung des Gründungsteams und der Mitarbeiter auf die innovativen Tätigkeiten junger Unternehmen. Für den Erfolg dieser Unternehmen sind, wie jüngere Untersuchungen gezeigt haben, alle Beteiligten (also Gründer und Mitarbeiter) wichtig. Wir nutzen eine von Ruef (2002) und Ruef et al. (2003) eingeführte Methode, die nicht nur auf der Anzahl der beteiligten Ethnien rekurriert, sondern die Wahrscheinlichkeit, dass eine bestimmte ethnische Zusammensetzung zustande kommt, berücksichtigt. Unsere Ergebnisse zeigen erstens, dass Ausländer eine wichtige Rolle als Unternehmer aber auch als Beschäftigte junger Unternehmen spielen. Zweitens können wir zeigen, dass nur wirklich seltene ethnische Kombinationen einen positiven Einfluss auf die Innovationswahrscheinlichkeit junger Unternehmen haben. Die Beteiligung relativ häufiger ethnischer Minderheiten dagegen wirkt sich tendenziell negativ auf die Innovationswahrscheinlichkeit aus.
Keywords: J15; J21; L26; M13; M14; 330; diversity; innovation; structural events analysis; start-ups